The Effect of Parkour for Disaster Preparedness Training on Psychological Preparedness for Disasters - Zharfani, Handy Aulia; Patria, Bhina (TDMRC, Universitas Syiah Kuala, 2024)
This study aims to determine the effect of parkour for disaster preparedness training on psychological preparedness for disasters. Parkour is predicted to be able to improve psychological preparedness for disasters because parkour practice develops flight response skills when a disaster occurs. This research was conducted using a quasi-experimental method involving 24 participants (11 males and 13 females) aged 15-18 years old, which assigned into the experimental group (n=11) and the control group (n=13). The experimental group was given general knowledge training on disasters (180 minutes) and parkour training for disaster preparedness (3 x 120 minutes), while the experimental group was only given general knowledge training on disasters. Measurements were made using the Psychological Preparedness for Disaster Threat Scale. The result of this study shows a significant difference in scores before and after the provision of general knowledge training in the experimental group (p=0.024) and the control group (p=0.012). However, there was no score change in the experimental group after the provision of parkour training for disaster preparedness (p=0.983), and there was no significant score decline in the control group that was not given any follow-up treatments (p=0.297). The final results showed no significant score difference between both groups (p=0.236). Therefore, this study concludes that general knowledge training on disasters effectively increases psychological preparedness for disasters, while the parkour for disaster preparedness training does not affect psychological preparedness for disasters because the parkour training provided was insufficient to develop flight response skills for disasters.